The real gaze : film theory after Lacan - McGowan, Todd (SUNY series in psychoanalysis and culture., 2007)
The Real Gaze develops a new theory of the cinema by rethinking the concept of the gaze, which has long been central in film theory. Historically film scholars have located the gaze on the side of the spectator; however, Todd McGowan positions it within the filmic image, where it has the radical potential to disrupt the spectator's sense of identity and challenge the foundations of ideology. This book demonstrates several distinct cinematic forms that vary in terms of how the gaze functions within the films. Through a detailed investigation of directors such as Orson Welles, Claire Denis, Stanley Kubrick, Spike Lee, Federico Fellini, Ron Howard, Steven Spielberg, Andrei Tarkovsky, Wim Wenders, and David Lynch, McGowan explores the political, cultural, and existential ramifications of these differing roles of the gaze.